Relationship between School Climate and Early Years Teachers Professional Identity in Kenya - Phyllis M. Magoma; Teresa Mwoma; Esther Waithaka (Randwick International of Education and Linguistics Science Journal, 2021)
This mixed methods research examined the relationship between school climate and early year’s teachers’ professional identity. Using a sample of 220 teachers in 44 schools, the researcher established that early years teachers’ professional identity was weak and school climate had an effect on the teachers’ professional identity. This article’s findings confirmed that among school climate variables safety in school, high teacher-pupil ratio, lack of adequate physical facilities, teachers not involved in decision making, poor working environment, heavy work load and lack of enough teaching-learning materials, as having a negative impact on the teachers professional identity. Lastly, in order to boost EYET (Early Years Education Teachers) professional identity, provision of positive climates in schools was found to be imperative.